Demand Valve Oxygen: A Promising New Oxygen Delivery System for the Acute Treatment of Cluster Headache - Rozen, Todd D.; Fishman, Royce S. (Pain medicine (Malden, Mass.), 2013)
Objective. To show that demand valve oxygen is an effective acute treatment for cluster headache and to compare this oxygen delivery technique with standard cluster headache therapy of continuous flow oxygen. Methods. Single‐center, open‐label, two‐period, two‐treatment crossover design, pilot study was used. Subjects treated with one of two sequences: first, headache treated with continuous flow oxygen (100% oxygen at 15 liters per minute), and subsequent with demand valve oxygen, or vice versa. Treatment began when pain was at least moderate. Subjects taught a specific breathing technique for demand valve oxygen that included initial period of hyperventilation. Primary end point was headache response (moderate‐to‐very‐severe pain reduced to mild or none) after 30 minutes of treatment. Results. Three subjects completed the trial, while a fourth completed demand valve oxygen only. All had chronic cluster headache. All subjects treated with demand valve oxygen became pain‐free (time in minutes: 15, 19, 6, 8). Three of four had no recurrence within 24 hours. Demand valve oxygen reduced cranial autonomic symptoms in all and resolved them in two subjects. For continuous flow oxygen, two of three subjects became pain‐free (20, 10 minutes). Continuous flow oxygen reduced but did not eliminate cranial autonomic symptoms. Continuous flow oxygen had higher recurrence rates. No adverse events noted with either treatment. Conclusion. Demand valve oxygen appears to be an effective acute treatment for cluster headache. All subjects became headache‐free. Time to pain freedom was fast (average 12 minutes). The small number of study subjects does not allow a direct comparison of efficacy between demand valve oxygen and continuous high flow oxygen.